Mihaela Jigău și Mihai Surdu (coordonatori), Participarea la educaţie a copiilor romi: probleme, soluţii, actori, Bucureşti, Editura MarLink, 2002 - Mihăilescu, Adina (Calitatea Vieții, 2002)
Without abstract